金属带式无级变速器液压控制系统对速比特性的影响分析 - 邹云飞; 胡纪滨; 苑士华; 陈智 (Jixie chuandong)
Taking the metal belt continuously variable transmission as an investigated object,the mathematical model of hydraulic control system is established based on the control system of ’force-displacement’. According to the model,the influence of the operating pressure of clamp force control valve,the switch frequency and rated flux of ratio control valve on the characteristic of ratio control is investigated. In addition,the influence of the supply oil of pump on clamp force is also investigated. The results show that the operating pressure and rated flux affect the response time of ratio control,the switch frequency affects the response quality and the supply oil affects the stability of the system pressure.